Functionalized Multi-Walled Carbon Nanotube/Cellulose Acetate Mixed Matrix Membrane For CO2/N2 Separation - Jawad, Zeinab Abbas (2014)

(untitled)
Carbon dioxide (CO2), as one of the major atmospheric contributors to the Earth's greenhouse effect has been rising extensively since the industrial revolution. One promising means of lowering the emission of CO2 is to develop highly efficient and robust membranes that are capable of selective CO2. Karbon dioksida (CO2) adalah salah satu penyumbang utama kepada kesan rumah hijau kepada bumi, yang kuantitinya kian meningkat sejak revolusi industri. Salah satu cara untuk mengurangkan pelepasan CO2 adalah dengan menghasilkan membran yang cekap dan mantap yang mampu menapis mengikut kememilihan CO2.